Airborne gravimetry takes off in the Western Australia 'Generation 2' reconnaissance gravity mapping project. Issue 1 (1st December 2018) - Howard, SHD; Brett, John; Lane, Richard; Richardson, Murray; Elieff, Stefan; Argyle, Malcolm
Abstract : In 1974, the Australian Bureau of Mineral Resources, Geology and Geophysics completed a 15-year systematic reconnaissance gravity survey of Australia with stations spaced at 11 km. The 1976 Gravity Map of Australia was a seminal product; half a century later, the data still provide the only coverage for substantial parts of the continent. In 2005, the Geological Survey of Western Australia, supported by Geoscience Australia, commenced a program of regional ground gravity surveys with 2.5 km station spacing, a sixteen-fold improvement of resolution over the 'first generation' BMR data. In 2013, GSWA declared its aim of completing 'second-generation' reconnaissance gravity coverage of WA by 2020. In 2016, with 45% of the State yet to be surveyed in the north and east, and ground access issues slowing progress and making uniform coverage increasingly difficult, GSWA and GA undertook the first government-commissioned regional aerogravity survey in Australia, using the Sander Geophysics AIRGrav system. The 38, 000 line-km survey covering 84, 000 km 2 in the East Kimberley region was flown at 2.5 km line-spacing for compatible spatial resolution with GSWA's regional ground surveys. We compare airborne with ground gravimetry in the context of the East Kimberley project and conclude that, for reconnaissance surveys: aerogravity costs now approach those of ground surveys; spatial resolution is equivalent; data precision is not a critical factor; and airborne and ground data can be merged seamlessly for interpretation. Consequently, new aerogravity surveys were commissioned over 264, 000 km 2 of northern WA in the Tanami, northeast Canning and Kidson regions.